Effect of nanobubbles on adsorption of sodium oleate on calcite surface. (15th March 2019) - Wang, Yunfan; Pan, Zuchao; Luo, Ximei; Qin, Wenqing; Jiao, Fen
Highlights: Nanobubbles are imaged on the surface of calcite. HPLC was used to measure the adsorption of NaOL on calcite. A device was designed to measure the adsorption of NaOL with nanobubbles. Nanobubbles inhibit the adsorption of NaOL on the surface of calcite. A model for nanobubbles to promote the formation of floc is proposed. Abstract: The aim of the study is to explore the effect of nanobubbles on the adsorption capacity of surfactants on mineral surfaces. Firstly, nanobubbles were imaged under the condition that the solution had a dissolved oxygen difference (DOD) by atomic force microscope (AFM). Subsequently, the calcite particles with 37–74 μm and sodium oleate (NaOL) were mixed and stirred under different mixing times and different pressure control (nanobubbles can be produced under the condition of decompression) through a self-made pressurization and decompression device. After nature sedimentation, the supernatant was extracted, and the change of the adsorption capacity of NaOL on the surface of calcite was detected by high performance liquid chromatography (HPLC). Finally, in order to study the direct influence of nanobubbles on the adsorption of NaOL on the surface of calcite, the NaOL on the surface of calcite were imaged under different pressure conditions by AFM. The experimental results showed that many nanobubbles were found on the calcite surface by AFM under the dissolved oxygen difference (DOD) condition of −4 mg/L. Furthermore, the order of adsorption of sodium oleate on the surface of calcite under different pressure conditions was as follows: constant low pressure (0.3 atm) > inflating (0.3 atm to 1 atm) > constant normal pressure (1 atm) > pumping gas (1 atm to 0.3 atm). More interestingly, compared with the constant pressure condition, the coverage of NaOL on the calcite surface was reduced under decompression pressure, about 30% lower at natural pH and about 20% lower at pH = 10, and this decrease was obvious. However, the change in adsorption height was considered by the author to be difficult to judge by AFM. The study concludes that nanobubbles can be generated under the condition that the DOD is less than 0. Moreover, nanobubbles not only promote the formation of floc, but also directly inhibit the adsorption of NaOL on the calcite surface, both reasons can inhibit the adsorption capacity of NaOL on the calcite surface. It provides a better idea and method for understanding of nanobubble, flotation, dissolved air flotation (DAF), and the interaction between surfactant and particles or particles and particles. These findings are benefit for these fields, such as mineral processing, biomedicine, etc.